Peningkatan Kemampuan Menyimak Anak Usia 5-6 Tahun Melalui Media Papan Flanel - Muznah; muz, muznah (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This study aims to improve the listening skills of 5-6 year old children at Satu Atap 01 Kindergarten through the use of flannel board media. This study was motivated by the low listening skills of children shown through lack of concentration, difficulty understanding the content of the story, and low ability to answer questions and retell the information heard. The study used the Classroom Action Research (CAR) method which was carried out in two cycles, with the stages of planning, implementation, observation, and reflection. The research subjects were 20 children of Group B. Data were collected through observation, interviews, and documentation, then analyzed descriptively qualitatively and quantitatively. The results showed that children's listening skills increased in each cycle. The percentage of developmental completeness increased from 15% in the pre-cycle to 60% in Cycle I and reached 90% in Cycle II. This improvement was seen in the children's ability to focus attention during storytelling activities, understand the content of the story, answer teacher questions correctly, follow verbal instructions, and retell the story coherently. These findings show that the use of flannel board media can improve the listening skills of children aged 5-6 years and can be used as an alternative, interesting learning media to support the development of language aspects in early childhood education.